Reframing the Arts within the Liberal Arts Community - Sarah Archino; Marta Lanier; Ross McClain (Artivate, 2020)
The dominance of New Venture Creation and Skills for Transitioning models has produced scholarship focusing on the impact of entrepreneurial pedagogy on graduates who pursue careers within the arts. This paper shares a liberal arts approach, positioning arts as a central component in the creation of an entrepreneurial mindset with benefits for students throughout campus. Shifting our department to cultivate an entrepreneurial mindset through arts-based experiential education, we have created an alternate approach that can serve those who wish to become professional artists, but also provides value for the majority of our students who will not remain in the arts.